Sporadic Goitre Prevalence and its Association with Iodine Deficiency in Drinking Water of Plain Areas of Hyderabad and Adjoining Areas, Pakistan - Rafi, M.; Naz, S.; Chaudhry, M. M. (The Nucleus, 2021)
The enlargement of thyroid gland which is located in the human neck is known as goitre. When the supply of iodine to the thyroid gland is inadequate for the formation of sufficient quantities of thyroid hormones, goitre appears. In the present study prevalence and epidemiological risk factors of goitre in Hyderabad city and adjoining areas has been studied. The important findings of this study are summarized as follows: Females were seen to be more prone to develop goitre than males, with an overall female to male ratio of 5:1. In both sexes, the prevalence of goitre was the maximum in 15-25 year age group. Family history was positive in 22.45% cases. Of the goitre patients 77.22% belonged to Hyderabad city and 84.85% were sedentary by occupation. Goitre was more prevalent in surface water drinkers (80.75%) than in ground water consumers (19.25%), in the consumers of mine salt (67.54%) than that of sea salt (32.46%). The screening of goitre patients by blood chemistry revealed that 5.17% and 2.50% cases had hyperthyroid and hypothyroid respectively. Nodular non-toxic goitre was found in 6.71% cases, nodular toxic in 0.28% cases and solid adenoma/cyst in 24.41% cases were found. It seemed essential to examine iodine concentration in water of this area to ascertain whether the iodine deficiency is the cause of sporadic goitre. Iodine concentration in water is usually taken as an index of the iodine intake, therefore 100 water samples were collected and analyzed by ion selective electrode method. Water analysis results showed that iodine contents are within permissible limit i.e. not lower than 3Âµg/L. This indicates that iodine deficiency in water of study area is not an isolated epidemiological phenomenon for goitre genesis.